Cadherin‐3 is a novel oncogenic biomarker with prognostic value in glioblastoma. Issue 14 (10th June 2022) - Martins, Eduarda P.; Gonçalves, Céline S.; Pojo, Marta; Carvalho, Rita; Ribeiro, Ana S.; Miranda‐Gonçalves, Vera; Taipa, Ricardo; Pardal, Fernando; Pinto, Afonso A.; Custódia, Carlos; Faria, Cláudia C.; Baltazar, Fátima; et al.
Abstract : Glioblastoma (GBM) is the most common and malignant primary brain tumor in adults. The prognosis of patients is very poor, with a median overall survival of 15 months after diagnosis. Cadherin‐3 (also known as P‐cadherin), a cell–cell adhesion molecule encoded by the CDH3 gene, is deregulated in several cancer types, but its relevance in GBM is unknown. In this study, we investigated the functional roles, the associated molecular signatures, and the prognostic value of CDH3 /P‐cadherin in this highly malignant brain tumor. CDH3 /P‐cadherin mRNA and protein levels were evaluated in human glioma samples. Knockdown and overexpression models of P‐cadherin in GBM were used to evaluate its functional role in vitro and in vivo . CDH3 ‐associated gene signatures were identified by enrichment analyses and correlations. The impact of CDH3 in the survival of GBM patients was assessed in independent cohorts using both univariable and multivariable models. We found that P‐cadherin protein is expressed in a subset of gliomas, with an increased percentage of positive samples in grade IV tumors. Concordantly, CDH3 mRNA levels in glioma samples from The Cancer Genome Atlas (TCGA) database are increased in high‐grade gliomas. P‐cadherin displays oncogenic functions in multiple knockdown and overexpression GBM cell models by affecting cell viability, cell cycle, cell invasion, migration, and neurosphere formation capacity. Genes that were positively correlated with CDH3 are enriched for oncogenic pathways commonly activated in GBM. In vivo, GBM cells expressing high levels of P‐cadherin generate larger subcutaneous tumors and cause shorter survival of mice in an orthotopic intracranial model. Concomitantly, high CDH3 expression is predictive of shorter overall survival of GBM patients in independent cohorts. Together, our results show that CDH3 /P‐cadherin expression is associated with aggressiveness features of GBM and poor patient prognosis, suggesting that it may be a novel therapeutic target for this deadly brain tumor. Abstract : Here, we identified Cadherin‐3 (CDH3) as a novel oncogene in glioblastoma (GBM). CDH3 affected distinct cancer hallmarks in vitro and was related to increased tumor growth and shorter survival in vivo . Clinically, CDH3 correlated with cancer‐related signatures and was overexpressed in a subset of patients with poor prognosis, thus suggesting that CDH3 could hold a prognostic value for patients with GBM (Scheme drawn with images from Servier Medical Art; https://smart.servier.com/ ).